A Systematic Review of Maternal and Child Health Policies in Addressing Stunting: Trends and Challenges - Pratiwi Ramlan; Phill Sukri; Muh. Tang Abdullah; Muhammad Akmal Ibrahim; Jamaluddin Ahmad; Khaeriyad Adri (Journal of Public Health and Pharmacy)
Introduction: Stunting, recognized as a prominent global health issue, particularly in low-income countries, arises from persistent undernutrition and frequent infections, adversely impacting children's physical development, cognitive abilities, and future economic productivity. Notwithstanding the implementation of various maternal and child health strategies designed to mitigate stunting, its incidence remains alarmingly high, exhibiting differential efficacy across diverse contexts due to obstacles in policy execution, accessibility issues, and socio-cultural influences.